Positive electrode active material for lithium secondary battery and lithium secondary battery using same
By preparing lithium composite phosphorus oxides with spherical shapes and uniform carbon coatings, the problem of low conductivity and energy density of the positive electrode active substance in lithium secondary batteries is solved, and a positive electrode active substance with high energy density is achieved.
Patent Information
- Application Number
- CN202411339923.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-26
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-29
AI Technical Summary
The conductivity and energy density of the positive electrode active substance in lithium secondary batteries are low, making it difficult to meet the high energy density needs of electric vehicles.
The slurry is prepared by mixing lithium-containing raw materials, transition metal precursors and carbon-based compounds, crushing and heat treatment to form lithium composite phosphorus oxides with spherical shapes and uniform carbon coatings.
The high compression density and excellent energy density of the positive electrode active substance are achieved, and the high energy density requirements of lithium secondary batteries in applications such as electric vehicles are met.
Smart Images

Figure CN119905541A_ABST
Abstract
Description
Technical Field
[0001] The present specification relates to a method for preparing a positive electrode active material for a lithium secondary battery, and more specifically, to a method for preparing a positive electrode active material for a lithium secondary battery having excellent electrical conductivity and energy density. Background Art
[0002] Batteries store electrical energy using materials capable of electrochemical reactions at the positive and negative electrodes. A typical example of such batteries is a lithium secondary battery that stores electrical energy by using the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.
[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] A variety of materials are used as positive electrode active materials for lithium secondary batteries, among which lithium metal phosphates, such as lithium iron phosphate (LiFePO 4 ) is widely used in the manufacture of lithium secondary batteries because of its excellent stability and ability to withstand multiple charge / discharge cycles, as well as its relatively low manufacturing cost.
[0005] However, due to the properties of lithium iron phosphate's olivine crystal structure, lithium ions can only diffuse in one dimension, resulting in low ionic conductivity and electrical conductivity. Therefore, there are technologies that attempt to nanosize lithium iron phosphate particles and perform carbon coating to improve these shortcomings.
[0006] However, nanosized lithium iron phosphate tends to aggregate due to the mutual attraction between particles and tends to grow into a shape that is not conducive to energy density.
[0007] Furthermore, carbon coating reduces the fluidity of lithium iron phosphate particles, which results in a decrease in the density of the positive electrode active material.
[0008] As technology develops, the demand for lithium secondary batteries, including electric vehicles, is increasing dramatically, and the demand for increased capacity of lithium secondary batteries, which is directly related to the use time of products, is also growing in related industries. Summary of the invention
[0009] Technical issues
[0010] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also changing. In particular, the demand for increased capacity of positive electrode active materials is gradually increasing.
[0011] In order to meet these market demands, an object of the present specification is to provide a method for preparing a positive electrode active material having an advantage in energy density by having a smooth spherical shape and including a uniform carbon coating layer.
[0012] In addition, the present specification aims to provide a positive electrode comprising a positive electrode active material prepared according to the preparation method defined herein.
[0013] Furthermore, the present specification aims to provide a lithium secondary battery using the positive electrode defined herein.
[0014] Solutions to the problem
[0015] According to one aspect of the present specification, a method for preparing a positive electrode active material for a lithium secondary battery is provided, comprising: step (a), preparing a slurry by mixing a lithium-containing raw material, a transition metal precursor and a carbon-based compound; step (b), crushing particles in the above slurry; and step (c), heat-treating the crushed particles to obtain a lithium composite phosphorus oxide; the ratio (B / A) of the solubility (B) of the above carbon-based compound in water at 25°C to the ratio (A) of the C element is 10.00 g / (L·wt%) or more.
[0016] In one embodiment, in the slurry in the step (a), the ratio (Li / Metal) of the number of lithium atoms (Li) to the total number of metal atoms (Metal) other than lithium may be 0.95 to 1.10.
[0017] In addition, in the slurry in the step (a), a ratio (C / Metal) of the number of carbon atoms (C) to the total number of metal atoms (Metal) other than lithium may be 0.03 to 0.1.
[0018] The ratio (B / A) of the solubility (B) of the carbon-based compound in water at 25° C. to the ratio (A) of the carbon element may be 30.00 g / (L·wt%) or more.
[0019] In addition, the carbon-based compound may be a compound having a ratio (A) of C element in a molecular structure of 30 wt % to 60 wt %.
[0020] In addition, the solubility (B) of the carbon-based compound in water at 25° C. may be 0 g / L to 3,000 g / L.
[0021] In one embodiment, in the above step (a), at least one auxiliary raw material including an element selected from the group consisting of Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, F, Fe, Ga, Hf, I, In, K, La, Mg, Mo, N, Na, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr may be further added to the above slurry.
[0022] Furthermore, the average particle size (D50) of the particles pulverized in the step (b) may be 1.0 μm or less.
[0023] On the other hand, the particles pulverized in the step (c) may be obtained by spray-drying the slurry obtained in the step (b).
[0024] In one embodiment, the heat treatment in the above step (c) may be performed at a maximum temperature of 300° C. to 1,000° C. for 5 to 12 hours in an inert atmosphere.
[0025] According to another aspect, a positive electrode active material for a lithium secondary battery is provided, which includes primary particles composed of lithium composite phosphorus oxide and secondary particles formed by agglomeration of multiple primary particles, the primary particles having a spherical shape, and an amorphous carbon coating with a thickness of 1 nm to 30 nm is formed on the surface of at least a portion of the primary particles.
[0026] On the other hand, the lithium composite phosphorus oxide can be represented by the following Chemical Formula 2.
[0027] [Chemical formula 2]
[0028] Li p M x A y B z P 1-z O w
[0029] In the above formula, M is at least one selected from the group consisting of Fe, Mn, Ni and Co, A is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Na, Nb, Nd, Os, Pd, Pr, Pt, Rh, Ru, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, B is at least one selected from the group consisting of C, Si, S, N, B, F, Cl and I, 0.5≤p≤1.5, 0 <x≤1、0≤y<1、0≤z<1、0<w≤4。
[0030] In addition, the carbon coating layer may be contained in an amount of 1.4 wt % to 1.8 wt % based on the total weight of the lithium composite phosphorus oxide.
[0031] According to another aspect, a positive electrode including the positive electrode active material is provided.
[0032] According to still another aspect, a lithium secondary battery using the positive electrode is provided.
[0033] Effects of the Invention
[0034] According to the present specification, when preparing a lithium composite phosphorus oxide by calcining a raw material, by including a carbon-based compound satisfying specific conditions, a spherical positive electrode active material having a smooth surface can be prepared.
[0035] Furthermore, when preparing the above-mentioned positive electrode active material, since the carbon coating layer is uniformly formed, a minimum amount of carbon-based compound can be used.
[0036] Therefore, the positive electrode active material has a high compression density and can have an excellent energy density.
[0037] In addition to the above-described effects, specific effects of the present specification will be described while explaining specific details of the present specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 FIG. 1 is a TEM image showing a positive electrode active material prepared according to an embodiment of the present disclosure.
[0039] Figure 2 The graph is a graph showing the relationship between the properties of the carbon-based compound in the positive electrode active material prepared according to one embodiment of the present specification and the thickness of the coating layer. DETAILED DESCRIPTION
[0040] Specific terms are defined herein to facilitate understanding of this specification. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.
[0041] Hereinafter, a method for preparing a positive electrode active material for a lithium secondary battery according to the present specification, a positive electrode including the positive electrode active material prepared according to the preparation method, and a lithium secondary battery using the positive electrode will be described in more detail.
[0042] Method for preparing positive electrode active material for lithium secondary battery
[0043] According to one aspect, a method for preparing a positive electrode active material for a lithium secondary battery includes: step (a), preparing a slurry by mixing a lithium-containing raw material, a transition metal precursor and a carbon-based compound; step (b), crushing particles in the above slurry; and step (c), heat-treating the crushed particles to obtain a lithium composite phosphorus oxide, wherein the ratio (B / A) of the solubility (B) of the above carbon-based compound in water at 25°C to the ratio (A) of the C element can be 10.00 g / (L·weight %) or more.
[0044] The above step (a) is a step of preparing an aqueous solution slurry by mixing a raw material for preparing a lithium composite phosphorus oxide with water.
[0045] The lithium-containing raw material used in the above step (a) is used to form a lithium complex phosphorus oxide used as a positive electrode active material, and lithium hydroxide, lithium carbonate, lithium nitrate, lithium phosphate, lithium fluoride or lithium acetate can be used.
[0046] At this time, mixing can be performed so that the ratio (Li / Metal) of the number of lithium atoms (Li) in the above-mentioned slurry of the above-mentioned lithium compound to the total number of metal atoms (Metal) other than lithium is in the range of 0.95 to 1.10, for example, it can be 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10 or a range between any two of these values.
[0047] On the other hand, the transition metal precursor is a precursor material of a lithium complex phosphorus oxide containing one or more transition metal elements, and can react with a lithium-containing raw material to form a lithium complex phosphorus oxide.
[0048] The above-mentioned transition metal may also include at least one transition metal such as iron, manganese, nickel, cobalt, vanadium, titanium, chromium, copper, zinc, etc. and at least one of the elements such as phosphorus, oxygen, hydrogen, carbon, silicon, sulfur, nitrogen, boron, fluorine, chlorine, iodine, etc.
[0049] On the other hand, the above transition metal precursor may include at least one transition metal and an anion.
[0050] Optionally, the transition metal precursor may be doped with a heterogeneous element. Here, the heterogeneous element may be at least one selected from the group consisting of Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, F, Fe, Ga, Hf, I, In, K, La, Mg, Mo, N, Na, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr.
[0051] As an example, the transition metal precursor may be an iron composite hydroxide or iron composite oxide containing iron, or an iron composite phosphorus oxide containing iron and phosphorus.
[0052] The iron composite hydroxide precursor can be prepared by a synthesis reaction in an aqueous solution containing an iron raw material.
[0053] As one example, the iron composite hydroxide precursor can be prepared by adding dropwise an alkaline aqueous solution to an aqueous solution containing an iron raw material, a phosphorus raw material, and an oxidizing agent while stirring the aqueous solution.
[0054] Here, the amount of the iron raw material, phosphorus raw material and oxidant added can be varied according to the composition of the desired positive electrode active material. 4 When the above-mentioned iron raw material, phosphorus raw material and oxidant are added, the difference in the amount of addition is less than 20% from each other on a molar basis, for example, 20%, 15%, 10% or a range between two of these values, but not limited to this.
[0055] In another example, the molar ratios of the iron raw material, the phosphorus raw material and the oxidant may be 0.8-1.2:0.8-1.2:0.8-1.2, i.e., 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2 or a molar ratio in a range between two of these values, but are not limited thereto.
[0056] On the other hand, a raw material containing a foreign element may be further selectively added to the above aqueous solution.
[0057] Here, examples of the above-mentioned iron raw material include ferrous sulfate, ferrous oxalate, ferric citrate, ferric hydroxide, ferric phosphate, ferric chloride, ferric nitrate, ferric acetate and the like.
[0058] On the other hand, as the phosphorus raw material, phosphoric acid, iron phosphate, lithium dihydrogen phosphate, lithium phosphate, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphorus pentoxide, and the like can be used.
[0059] In addition, examples of the above-mentioned oxidizing agent include hydrogen peroxide, glycolic acid, citric acid, ammonium persulfate, sodium persulfate, potassium persulfate, potassium permanganate, ammonium persulfate, nitric acid, chloric acid, chromic acid, manganese dioxide, ferric chloride and the like.
[0060] As the alkaline aqueous solution, a sodium hydroxide aqueous solution, an ammonia aqueous solution, a potassium hydroxide aqueous solution or the like can be used.
[0061] The above-mentioned alkaline aqueous solution is added to an aqueous solution in which an iron raw material, a phosphorus raw material and an oxidant are added to pure water (DIW), and the reaction is carried out at a temperature of 40°C to 80°C, for example, at 40°C, 42.5°C, 45°C, 47.5°C, 50°C, 52.5°C, 55°C, 57.5°C, 60°C, 62.5°C, 65°C, 67.5°C, 70°C, 72.5°C, 75°C, 77.5°C, 80°C or a temperature in a range between any two of these values, to prepare a hydroxide precursor.
[0062] The above reaction can be carried out under inert conditions, for example, in the presence of a 2 The method is carried out in a reaction system substituted with at least one inert gas selected from the group consisting of Ar, He, Rn, Ne and Xe, but is not limited thereto.
[0063] On the other hand, as necessary, a raw material containing a foreign element may be further added to dope the hydroxide precursor with the foreign element.
[0064] The iron composite oxide precursor can be prepared by heat-treating the above-mentioned iron composite hydroxide precursor.
[0065] Here, the iron composite oxide precursor may be heat-treated in a calcining furnace at 400° C. to 700° C., for example, 400° C., 425° C., 450° C., 475° C., 500° C., 525° C., 550° C., 575° C., 600° C., 625° C., 650° C., 675° C., 700° C., or the highest temperature within any two temperature ranges therebetween, for 3 hours to 10 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, or any two times within these time ranges, but is not limited thereto.
[0066] On the other hand, the heat treatment is performed at a temperature increase rate of 1°C to 5°C per minute, for example, at a temperature increase rate of 1°C, 1.5°C, 2°C, 2.5°C, 3°C, 3.5°C, 4°C, 4.5°C, 5°C or a range between any two of these values per minute, so that the above maximum temperature can be reached. In addition, the heat-treated precursor can be obtained by furnace cooling.
[0067] Using the iron composite oxide precursor prepared in this manner, nano primary particles having an olivine crystal structure can be formed.
[0068] As a specific example, the above-mentioned iron composite oxide precursor is prepared by the following steps: step (i), preparing an iron composite hydroxide precursor by adding an alkaline aqueous solution to a reaction system containing an iron raw material, a phosphorus raw material and an oxidant; and step (ii), preparing an iron composite oxide precursor by heat treating the above-mentioned iron composite hydroxide precursor, but is not limited to this.
[0069] In another example, the transition metal precursor may be represented by the following Chemical Formula 1.
[0070] [Chemical formula 1]
[0071] M x A y B z P 1-z O w
[0072] (In the above formula, M is at least one selected from the group consisting of Fe, Mn, Ni and Co, A is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Na, Nb, Nd, Os, Pd, Pr, Pt, Rh, Ru, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, B is at least one selected from the group consisting of C, Si, S, N, B, F, Cl and I, 0 <x≤1,0≤y<1,0≤z<1,0<w≤4)
[0073] The transition metal precursor represented by the above chemical formula 1 is an oxide precursor and can be prepared by heat treating sulfate, carbonate, nitrate, acetate, silicate, phosphate, borate, fluoride, chloride or hydroxide. For example, FePO 4 The following are non-limiting examples of the above Chemical Formula 1.
[0074] On the other hand, the carbon-based compound contained in the slurry in the above step (a) may be used to form a carbon coating layer that improves the electrical conductivity of the positive electrode active material.
[0075] For example, lithium iron phosphate-based compounds as olivine-based cathode materials have a 4 3- The strong covalent bond of Li has a relatively low conductivity. In addition, it is known that due to its crystal structure, Li + Only one-dimensional diffusion is possible, so its ionic conductivity is low.
[0076] As a means to solve these shortcomings, a technique of improving the conductivity by forming a carbon coating and a technique of improving the conductivity of Li by nanoparticle formation have been proposed. + Diffusion of technology.
[0077] However, the coated carbon exists in an amorphous phase, thereby possibly reducing the density of the positive electrode active material.
[0078] In one embodiment, the carbon-based compound may be a compound of formula C x H y O z +nH 2 O or Me a+ (C x H y O z +nH 2 O) a- wherein y may be 2x or 2(xn), and z may be x or xn, but is not limited thereto. On the other hand, Me may be a metal element, and a may be an integer from 1 to 4, i.e., 1, 2, 3 or 4.
[0079] Examples of the above-mentioned carbon-based compounds include sucrose, glucose, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), colloidal carbon, citric acid, tartaric acid, glycolic acid, polyacrylic acid, adipic acid, glycine, aminobenzoic acid, etc., but are not limited thereto.
[0080] On the other hand, the nanosized particles grow into angular particles due to agglomeration during the calcination process.
[0081] As a result, the density of the positive active material is reduced due to decreased fluidity and angled particles caused by amorphous carbon, which may reduce the energy density of the final product.
[0082] When the thickness of the carbon coating layer is minimized while increasing its uniformity, a decrease in fluidity due to amorphous carbon can be minimized, and the conductivity of the positive active material can be improved.
[0083] Among them, by controlling the properties of the above-mentioned carbon-based compound, the properties of the carbon coating formed on the positive electrode active material can be adjusted.
[0084] As an example, the above-mentioned carbon-based compound can be added so that the ratio (C / Metal) of the number of carbon atoms (C) to the total number of metal atoms (Metal) other than lithium in the above-mentioned slurry is in the range of 0.03 to 0.1, for example, it can be 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or a range between any two of these values.
[0085] On the other hand, the above-mentioned carbon-based compound can be added so that the content of the carbon coating in the final product is 1.4 wt % to 1.8 wt %, for example, 1.4 wt %, 1.45 wt %, 1.5 wt %, 1.55 wt %, 1.6 wt %, 1.65 wt %, 1.7 wt %, 1.75 wt %, 1.8 wt %, or a range between any two of these values, based on 100 wt % of the lithium composite phosphorus oxide.
[0086] If the content of the carbon-based compound in the slurry satisfies the above range, a thin carbon coating layer can be easily formed.
[0087] On the other hand, the properties of the formed carbon coating layer can be varied depending on the solubility of the carbon-based compound in water at 25° C. (B) and the ratio of the C element (A).
[0088] The above method forms a carbon coating in a slurry which is an aqueous solution. That is, the above method is based on the fact that the properties of the carbon coating change according to the ratio of the solubility of the above carbon-based compound in water to the ratio of the C element.
[0089] For example, when their ratio (B / A) is 10g / (L·weight%) or more, for example, when their ratio (B / A) is 10g / (L·weight%), 11g / (L·weight%), 12g / (L·weight%), 13g / (L·weight%), 14g / (L·weight%), 15g / (L·weight%), 16g / (L·weight%), 17g / (L·weight%), 18g / (L·weight%), 19g / (L·weight%), 20g / (L·weight%), 21g / (L·weight%), 22g / (L·weight%), 23g / (L·weight%), 24g / (L·weight%), 25g / (L·weight%), 26g / (L·weight%), 27g / (L·weight%), 28g / (L·weight%), 29g / · wt %, 30g / (L·wt %), 31g / (L·wt %), 32g / (L·wt %), 33g / (L·wt %), 34g / (L·wt %), 35g / (L·wt %), 36g / (L·wt %), 37g / (L·wt %), 38g / (L·wt %), 39g / (L·wt %), 40g / (L·wt %), 41g / (L·wt %), 42g / (L·wt %), 43g / (L·wt %), 44g / (L·wt %), 45g / (L·wt %), 46g / (L·wt %), 47g / (L·wt %), 48g / (L·wt %), 49g / (L·wt %), 50g / (L·wt %) or more, a thinner carbon coating can be uniformly formed.
[0090] Specifically, in one example, if the ratio (B / A) of the solubility (B) of the above-mentioned carbon-based compound in water at 25°C to the ratio of the C element (A) is 30.00 g / (L·weight %) or higher, a more uniform and thinner carbon coating can be formed.
[0091] As described above, when the B / A value satisfies the above range and the slurry in the above step (a) is used to prepare a lithium iron phosphate-based compound, a carbon coating having a thickness of 1 nm to 30 nm, for example, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 12.5 nm, 15 nm, 17.5 nm, 20 nm, 22.5 nm, 25 nm, 27.5 nm, 30 nm or a range between any two of these values can be uniformly formed.
[0092] Although its mechanism of action is not yet clear, if the carbon-based compound contained in the above slurry meets the above conditions, it is possible that the lithium iron phosphate-based compound raw material is fully dispersed and forms a uniform carbon coating.
[0093] On the other hand, the above-mentioned carbon-based compound can be a compound having a C element ratio in the molecular structure of 30% to 60% by weight, for example, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% by weight, or a range between any two of these values.
[0094] By using a carbon-based compound having a ratio of the C element satisfying the above range, a product having excellent yield and carbon coating uniformity can be prepared even if the same content of the compound is used.
[0095] Since the above-mentioned preparation method uses a wet coating method to form the carbon coating layer, it is necessary to use a raw material having sufficient solubility in water.
[0096] Therefore, the solubility of the above-mentioned carbon-based compounds in water at 25°C can be 0 g / L to 3,000 g / L, for example, 3,000 g / L, 2,750 g / L, 2,500 g / L, 2,250 g / L, 2,000 g / L, 1,750 g / L, 1,500 g / L, 1,250 g / L, 1,000 g / L, 750 g / L, 500 g / L, 250 g / L, 200 g / L, 150 g / L, 100 g / L, 50 g / L or a range between any two of these values.
[0097] If a carbon-based compound having a solubility within the above range is used, a uniform coating can be formed more easily.
[0098] In addition, the carbon-based compound needs to be carbonized within the heat treatment temperature of step (c). If uncarbonized carbon-based compound remains in the positive electrode active material, the improvement in conductivity may be minimal or unexpected side effects may occur.
[0099] In one embodiment, in the above step (a), at least one auxiliary raw material including an element selected from the group consisting of Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, F, Fe, Ga, Hf, I, In, K, La, Mg, Mo, N, Na, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr may be further added to the above slurry.
[0100] If an auxiliary raw material is further added in the step (a), an element not included in the transition metal precursor can be doped, or the ratio of the elements included in the transition metal precursor can be adjusted.
[0101] Next, the step (b) is a step of pulverizing the particles in the slurry. Here, the lithium-containing raw material, transition metal precursor, etc. may be present in the slurry in the form of particles.
[0102] In order to pulverize the above-mentioned particles, a dry or wet dispersion mill such as a ball mill, a bead mill (beads such as aluminum beads, iron beads or zirconium beads, which are generally used to pulverize metallic raw materials, can be used), a vibratory mill, an attritor mill, an air jet mill, a disc mill or an air classifier mill can be used.
[0103] The average particle size (D50) of the particles crushed in the step (b) may be less than 1 μm, for example, 1.0 μm, 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm, 0.5 μm, 0.4 μm, 0.3 μm, 0.2 μm, 0.1 μm or a range between any two of these values.
[0104] The particles pulverized to have an average particle size within the above range are easily aggregated due to surface energy. During the calcination process, the aggregated particles grow into horn shapes, resulting in a decrease in the density of the positive electrode active material.
[0105] Aggregation can be suppressed by using a specific carbon-based compound to activate the interface of the particles and generate electrostatic force on the surface. As a result, the particles grow into spherical shapes, which can improve density characteristics.
[0106] On the other hand, after the pulverization in step (b), the slurry may be dried to obtain a powder form. For example, the slurry may be dried by spray drying. That is, the particles pulverized in step (c) may be obtained by spray drying the slurry obtained in step (b).
[0107] Spray drying as an example of the above-mentioned drying can be carried out in a spray dryer. As the above-mentioned spray dryer, there is no particular limitation as long as it is a spray drying device that can prepare nearly spherical dry particles by spray-drying the above-mentioned slurry containing the above-mentioned crushed particles. For example, an ultrasonic sprayer, a single-fluid nozzle sprayer, a two-fluid nozzle sprayer, an ultrasonic nozzle sprayer, a filter expansion droplet generator (FEAG) or a disc droplet generator can be used.
[0108] The spray dryer may include a spray nozzle and a drying chamber, and the slurry is atomized into droplets of a predetermined size through the spray nozzle and sprayed into the drying chamber where a relatively high temperature gas flows.
[0109] The raw material in the liquid droplets sprayed into the drying chamber may be dried into nearly spherical particles under the temperature environment in the drying chamber.
[0110] On the other hand, if the slurry contains a specific carbon-based compound, unnecessary aggregation of the particles during spray drying can be suppressed, and as a result, particles close to spherical shapes can be obtained.
[0111] Here, when the viscosity of the slurry is adjusted after the pulverization in step (b) is completed, the aggregation time during drying can be shortened, and the decrease in density due to water loss during drying can be minimized.
[0112] Water loss during drying reduces particle density and forms pores. As a result, particle strength may decrease, leading to insufficient stability of the positive electrode active material.
[0113] On the other hand, if the viscosity of the slurry is too high, the fluidity decreases during drying, resulting in insufficient process efficiency and difficulty in obtaining spherical particles.
[0114] One of the methods for adjusting the viscosity of the above slurry is to add a binder.
[0115] Subsequently, the step (c) may be a step of heat-treating the particles pulverized in the step (b) to form a lithium composite phosphorus oxide.
[0116] During the heat treatment in step (c), the carbon-based compound may be carbonized to form a carbon coating.
[0117] The heat treatment in the above step (c) may be carried out in an inert atmosphere at 300°C to 1,000°C, for example, at 300°C, 325°C, 350°C, 375°C, 400°C, 425°C, 450°C, 475°C, 500°C, 525°C, 550°C, 575°C, 600°C, 625°C, 650°C, 675°C, 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C, 875°C. , 900°C, 925°C, 950°C, 975°C, 1,000°C or the maximum temperature of the range between any two of these values for 5 to 12 hours, for example, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours or the time of the range between any two of these values. At this time, the above-mentioned maximum temperature can vary according to the composition of the target positive active material.
[0118] More specifically, the heat treatment in the step (c) may be performed in a calcining furnace while maintaining an inert atmosphere at a rate of 2°C to 5°C per minute to 300°C to 1,000°C for 5 to 12 hours. When the heat treatment temperature in the step (c) is lower than 300°C, the calcination of the precursor is not sufficiently performed, so that the crystal growth of the lithium composite phosphorus oxide may be insufficient, or it may be difficult to form a carbon coating. On the other hand, when the heat treatment temperature in the step (c) exceeds 1,000°C, the lithium composite phosphorus oxide may be thermally decomposed, resulting in reduced particle strength or particle collapse.
[0119] Here, for example, the inert atmosphere gas may be selected from N 2 , Ar, He, Rn, Ne and Xe instead of air.
[0120] Optionally, in the above step (c), before the above particles crushed in the above step (b) are heat-treated, at least one of a secondary raw material and a lithium-containing raw material selected from the group consisting of Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, F, Fe, Ga, Hf, I, In, K, La, Mg, Mo, N, Na, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr may be further added. The secondary raw material may be provided in the form of at least one selected from sulfate, carbonate, nitrate, acetate, chloride, hydroxide and oxide.
[0121] At this time, the content of the auxiliary material added in the step (c) may vary depending on the composition of the particles and the composition of the target positive electrode active material.
[0122] Therefore, when the mixture of the particles and the auxiliary material is heat treated in the step (c), the elements contained in the auxiliary material may be doped into the lithium composite phosphorus oxide or may be coated on at least a portion of the surface of the lithium composite phosphorus oxide.
[0123] The lithium complex phosphorus compound obtained in the step (c) may include primary particles and secondary particles formed by agglomeration of the primary particles. The lithium complex phosphorus compound may be represented by the following chemical formula 2, but is not limited thereto.
[0124] [Chemical formula 2]
[0125] Li p M x A y B z P 1-z O w
[0126] (In the above formula, M is at least one selected from the group consisting of Fe, Mn, Ni and Co, A is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Na, Nb, Nd, Os, Pd, Pr, Pt, Rh, Ru, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, B is at least one selected from the group consisting of C, Si, S, N, B, F, Cl and I, 0.5≤p≤1.5, 0 <x≤1、0≤y<1、0≤z<1、0<w≤4)
[0127] In addition, before or after the step (c), the lithium composite phosphorus oxide may be subjected to a pulverization (disintegration), classification (distribution) and / or water washing process.
[0128] Positive electrode active material for lithium secondary battery
[0129] According to another aspect, a positive electrode active material for a lithium secondary battery may include primary particles composed of lithium composite phosphorus oxide and secondary particles formed by agglomeration of multiple primary particles. The primary particles may have a spherical shape, and an amorphous carbon coating with a thickness of 1 nm to 30 nm may be formed on the surface of at least a portion of the primary particles.
[0130] The positive electrode active material is provided as an aggregate including primary particles composed of a lithium complex phosphorus oxide capable of absorbing and releasing lithium ions and secondary particles formed by aggregating the primary particles.
[0131] Wherein, the primary particle refers to a crystal grain (grain or crystallite), and the secondary particle refers to an aggregate formed by agglomeration of a plurality of primary particles. The primary particle may have a spherical shape. As described above, since the lithium composite phosphorus oxide prepared according to the method is a particle having a smooth surface, the positive electrode active material may have an excellent compression density.
[0132] Pores and / or grain boundaries may exist between the primary particles constituting the secondary particles. In another embodiment, the positive electrode active material may include a lithium composite phosphorus oxide in the form of a single crystal having an average particle size of 0.1 μm or more.
[0133] The primary particles may be spaced apart from adjacent primary particles in the interior of the secondary particles to form internal pores. In addition, the primary particles may form a surface present in the interior of the secondary particles by contacting the internal pores, without forming a grain boundary by contacting adjacent primary particles. On the other hand, the surface of the primary particles present in the outermost surface of the secondary particles exposed to the external air forms the surface of the secondary particles.
[0134] Among them, when the average particle size of the above-mentioned primary particles (here, the average particle size of the above-mentioned primary particles may be the average major axis length of the above-mentioned primary particles) is in the range of 0.2μm to 1.0μm, the optimal density of the positive electrode prepared using the positive electrode active material according to various embodiments can be achieved.
[0135] The average particle size of the secondary particles formed by agglomeration of a plurality of the primary particles described above may vary depending on the number of agglomerated primary particles, but may generally be 30.0 μm to 40.0 μm.
[0136] The compression density of the positive electrode active material may be 2.30 g / cc or more. On the other hand, the positive electrode active material may have an energy density of 1,200 Wh / kg or more. By applying the above method, a positive electrode active material having high compression density and high energy density may be prepared.
[0137] In one example, the lithium composite phosphorus oxide may be represented by the following Chemical Formula 2.
[0138] [Chemical formula 2]
[0139] Li p M x Ay B z P 1-z O w
[0140] (In the above formula, M is at least one selected from the group consisting of Fe, Mn, Ni and Co, A is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Na, Nb, Nd, Os, Pd, Pr, Pt, Rh, Ru, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, B is at least one selected from the group consisting of C, Si, S, N, B, F, Cl and I, 0.5≤p≤1.5, 0 <x≤1、0≤y<1、0≤z<1、0<w≤4)
[0141] The composition of the lithium composite phosphorus oxide may vary depending on the composition of the raw material used in the above-mentioned preparation method and the type and composition of the auxiliary raw material additionally used therein.
[0142] Furthermore, the positive electrode active material may include a coating layer covering at least a portion of the surface of the primary particles (eg, interfaces between the primary particles) and / or secondary particles formed by agglomerating the primary particles.
[0143] For example, the coating may exist in a manner of covering at least a portion of the exposed surface of the primary particle. In particular, the coating may exist in a manner of covering at least a portion of the exposed surface of the primary particle present at the outermost periphery of the secondary particle.
[0144] Thus, the coating layer may exist as a layer that continuously or discontinuously coats the surface of the primary particles and / or the secondary particles formed by agglomerating the primary particles. When the coating layer exists discontinuously, it may exist in the form of islands.
[0145] Furthermore, depending on circumstances, the oxide may exist not only at the interface between the primary particles and at least a portion of the surface of the secondary particles, but also in internal voids formed in the secondary particles.
[0146] The presence of the coating in this manner can contribute to improving the electrochemical characteristics and stability of the positive electrode active material.
[0147] The coating layer may exist in the form of a solid solution without forming a boundary with the primary particles and / or the secondary particles formed by agglomerating the primary particles, but the coating layer is not necessarily limited thereto.
[0148] In particular, the low conductivity of lithium iron phosphate-based cathode active materials can be compensated by carbon coating. However, uneven carbon coating may deteriorate the properties of the cathode active materials such as BET specific surface area, compression density and energy capacity.
[0149] Among them, the content of the above-mentioned carbon coating can be 1.4 wt% to 1.8 wt% based on 100 wt% of the above-mentioned lithium composite phosphorus oxide, for example, 1.4 wt%, 1.45 wt%, 1.5 wt%, 1.55 wt%, 1.6 wt%, 1.65 wt%, 1.7 wt%, 1.75 wt%, 1.8 wt% or a range between two of these values.
[0150] When the above range is satisfied, the electrical conductivity of the lithium composite phosphorus oxide can be improved, and at the same time, the reduction in the compression density of the positive electrode active material can be minimized.
[0151] For example, the thickness of the amorphous carbon coating formed on at least a portion of the surface of the primary particles may be from 1 nm to 30 nm, for example, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 12.5 nm, 15 nm, 17.5 nm, 20 nm, 22.5 nm, 25 nm, 27.5 nm, 30 nm or a range between any two of these values.
[0152] In a non-limiting example, the thickness of the carbon coating may be 10 nm or less. In order to form a uniform carbon coating of 10 nm or less, it is necessary to use a carbon-based compound having a ratio (B / A) of solubility (B) to C element ratio (A) of 10.00 g / (L·wt%) or more in water at 25°C.
[0153] The thickness of the carbon coating layer can be adjusted according to the balance between the fluidity and the conductivity of the lithium composite phosphorus oxide.
[0154] The thickness of the carbon coating can be measured using a variety of known methods. For example, it can be measured by TEM or SEM images, or confirmed by EDX analysis results or line scanning inspection results of carbon in a specific direction. The thickness as described above can be an average value after at least 3 measurements.
[0155] In particular, the carbon coating layer has a small thickness deviation, so the positive electrode active material has an excellent balance between fluidity and conductivity, which have a complementary relationship.
[0156] For example, in the above-mentioned carbon coating, the thickness difference between the thickest area and the thinnest area can be less than 10nm, for example, it can be 10nm, 9.5nm, 9nm, 8.5nm, 8nm, 7.5nm, 7nm, 6.5nm, 6nm, 5.5nm, 5nm, 4.5nm, 4nm, 3.5nm, 3nm, 2.5nm, 2nm, 1.5nm, 1nm, 0.9nm, 0.8nm, 0.7nm, 0.6nm, 0.5nm, 0.4nm, 0.3nm, 0.2nm, 0.1nm or a range between any two of these values.
[0157] By using a carbon-based compound that satisfies specific conditions, the above-mentioned carbon coating layer can be formed thinly and uniformly.
[0158] On the other hand, the performance of the positive electrode active material may be improved according to the characteristics of the carbon-based compound used to form the carbon coating layer.
[0159] For example, if the carbon coating layer is formed using a carbon-based compound having a high ratio (B / A) of solubility (B) to ratio (A) of carbon element in water at 25° C., the capacity and compression density of the positive electrode active material can be excellent.
[0160] Lithium secondary battery
[0161] According to another aspect, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector may be provided, wherein the positive electrode active material layer may include a positive electrode active material prepared by the preparation method according to various embodiments as the positive electrode active material.
[0162] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be surface treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.
[0163] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.
[0164] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.
[0165] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0166] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.
[0167] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.
[0168] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when coated for the preparation of the positive electrode.
[0169] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.
[0170] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.
[0171] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte interposed between the positive electrode and the negative electrode.
[0172] In addition, the lithium secondary battery can be provided as an anode-free secondary battery. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not mentioned above is described below. In addition, the description related to the negative electrode to be described below should be understood as being described on the premise that the negative electrode is present in the lithium secondary battery.
[0173] On the other hand, the lithium secondary battery may be a lithium secondary battery using a solid electrolyte instead of a separator. In this case, an electrode slurry composition to which an additional solid electrolyte is added may be used when preparing the positive electrode and the negative electrode.
[0174] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.
[0175] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0176] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3μm to 500μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as film, sheet, foil, net, porous body, foam, non-woven body, etc.
[0177] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.
[0178] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β (0<β<2), SnO 2 , vanadium oxide, lithium vanadium oxide, a metal oxide capable of being doped and dedoped with lithium; or a composite containing the above metal compound and a carbon material such as a Si-C composite or a Sn-C composite, etc., one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbon is soft carbon (soft carbon) and hard carbon (hard carbon), and representative high-crystalline carbon is amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Me sophase pitches) and petroleum or coal tar pitch derived coke (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbon.
[0179] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.
[0180] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0181] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0182] In one embodiment, the negative electrode active material layer can be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.
[0183] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane comprising a ceramic component and a coated polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.
[0184] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.
[0185] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0186] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.
[0187] The lithium salt may be any compound that can provide lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF 6 、LiClO 4 、LiAsF6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 , LiCl, LiI or LiB(C 2 O 4 ) 2 etc. Preferably, the concentration of the lithium salt is used in the range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and thus can show excellent electrolyte performance and enable lithium ions to move efficiently.
[0188] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.
[0189] On the other hand, the above-mentioned electrolyte may include a solid electrolyte such as a solid polymer electrolyte, a gel-type polymer electrolyte, or a solid inorganic electrolyte.
[0190] A lithium secondary battery containing a solid electrolyte can omit the above-mentioned separation membrane. However, since it is difficult for the electrolyte to penetrate into the positive electrode and the negative electrode, the electrode can be formed by mixing the solid electrolyte when manufacturing the electrode.
[0191] On the other hand, the solid polymer electrolyte or gel polymer electrolyte can be a composite of a salt of a metal ion of Group 1 or Group 2 of the periodic table and a polymer resin. For example, it can be formed by adding a polymer resin to a solvated lithium salt.
[0192] The salt of the above metal ion can be LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 , LiCl, LiI or LiB(C 2 O 4 ) 2 wait.
[0193] For example, examples of the above-mentioned polymer resin can be polyether polymers, polycarbonate polymers, acrylic polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives, alkyl oxide derivatives such as polyethylene glycol, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionic dissociative groups, branched copolymers in which amorphous polymers such as PMM A, polycarbonate, polysiloxane (PDMS) or phosphazene are copolymerized as comonomers in the PEO (polyethylene glycol) main chain, comb-like polymer resins, and cross-linked polymer resins.
[0194] As the solid inorganic electrolyte, generally a sulfide-based solid electrolyte and an oxide-based solid electrolyte can be used.
[0195] Sulfide-based solid electrolytes may be materials containing sulfur (S) and having conductivity of metal ions of Group 1 or Group 2 of the periodic table used in secondary batteries, such as Li-PS-based glass or Li-PS-based glass ceramics having lithium ion conductivity.
[0196] Examples of the above-mentioned sulfide-based solid electrolyte may be selected from Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I. Li 2 SP 2 S 5 , Li 2 S-LiI-P 2 S 5 , Li 2 S-LiI-Li 2 OP 2 S 5 , Li 2 S-Li Br-P 2 S 5 , Li 2 S-Li 2 OP 2 S 5 , Li 2 S-Li 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 -P 2 S 5 , Li 2 SP 2 S 5 -SiS 2 , Li 2 SP 2 S 5 -SnS、Li 2 SP 2 S 5 -Al 2 S 3 , Li 2 S-GeS 2 Li 2 S-GeS 2 - At least one member of the group consisting of ZnS.
[0197] On the other hand, the oxide-based solid electrolyte may be a material containing oxygen (O) and having the conductivity of metal ions of Group 1 or Group 2 of the periodic table used in secondary batteries. For example, examples of the above-mentioned oxide-based solid electrolyte may be selected from LLTO-based compounds, Li 6 La 2 CaTa 2 O 12 , Li 6 La 2 AHr 2 O 12 , Li 6 La 2 AHr 2 O 12 , Li 2 Nd 3 T8h 12 , Li 3 BO 2.5 N 0.5 , Li 9 SiAlO 8 , at least one of the group consisting of LAGP-based compounds, LATP-based compounds, LISICON-based compounds, LIPON-based compounds, perovskite-based compounds, NASICO-based compounds and LLZO-based compounds.
[0198] As described above, the lithium secondary battery containing the above-mentioned positive electrode active material stably shows excellent discharge capacity, output characteristics and life characteristics, and therefore can be used in portable devices such as mobile phones, notebook computers, digital cameras and electric vehicle fields such as hybrid electric vehicles (HEV).
[0199] The shape of the lithium secondary battery is not particularly limited, and may be a cylindrical can, a prismatic can, a pouch can, a coin can, etc. Preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.
[0200] According to another aspect, a battery module including the above-described lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.
[0201] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.
[0202] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.
[0203] Preparation Example 1. Preparation of positive electrode active material
[0204] (1) Embodiment 1
[0205] Add FeSO to the reactor 4 7H 2 O, H 3 PO 4 and H 2 O 2 , making FeSO 4 7H 2 O, H 3 PO 4 and H 2 O 2 The molar ratio of NH4OH to NH4OH was 1:1:1, and then pure water (DIW) was added to prepare an aqueous solution. 4 OH and stirred. At this time, the temperature in the reactor was maintained at 60°C and N 2 After the reaction is completed, the precursor is washed and dehydrated to obtain a composition of FePO 4 ·xH 2 O hydroxide precursor.
[0206] In N 2 The transition metal hydroxide precursor was heat-treated for 5 hours in a calcining furnace with an atmosphere of 2°C / min to 550°C and maintained at this temperature, and then furnace-cooled to obtain a transition metal precursor.
[0207] By mixing the above transition metal precursor, Li 2 CO 3 Sucrose (C 12 H 22 O 11) to prepare the slurry. The lithium-containing raw material is weighed so that the lithium / metal molar ratio is 1.00, and the carbon-based compound is weighed so that the carbon / metal molar ratio is 0.03 to 0.1. Then, the precursor and raw material in the slurry are crushed using a bead mill so that D50 is less than 1.0 μm. Then, a spray dryer (Dongjin Technology Co., Ltd., South Korea, DJE003R) is used to dry the above slurry.
[0208] In N 2 The mixture was heat treated for 8 hours in a calcining furnace with a temperature of 2°C / min up to 850°C and maintained at this temperature. Then, by furnace cooling and classification, a positive electrode active material containing lithium iron phosphate having a secondary particle D50 of 30.0 μm to 40.0 μm and a primary particle D50 of 0.2 μm to 1.0 μm was obtained.
[0209] (2) Embodiment 2
[0210] In addition to using maltose (C 12 H 22 O 11 ) was used instead of sucrose as the carbon-based compound, and the positive electrode active material was prepared in the same manner as in Example 1.
[0211] (3) Embodiment 3
[0212] In addition to using glucose (C 6 H 12 O 6 ) was used instead of sucrose as the carbon-based compound, and the positive electrode active material was prepared in the same manner as in Example 1.
[0213] (4) Embodiment 4
[0214] In addition to using ethylene glycol (PEG; C 2n H 4n+2 O n+1 ) was used instead of sucrose as the carbon-based compound, and the positive electrode active material was prepared in the same manner as in Example 1.
[0215] (5) Embodiment 5
[0216] In addition to using carboxymethyl cellulose (CMC; -CH 2 The positive electrode active material was prepared in the same manner as in Example 1, except that sucrose was replaced by 2-COOH) as the carbon-based compound.
[0217] (6) Embodiment 6
[0218] In addition to using polyacrylic acid (PAA; (C 3 H 4 O 2 )n ) was used instead of sucrose as the carbon-based compound, and the positive electrode active material was prepared in the same manner as in Example 1.
[0219] (7) Embodiment 7
[0220] In addition to using lactose (C 12 H 22 O 11 ) was used instead of sucrose as the carbon-based compound, and the positive electrode active material was prepared in the same manner as in Example 1.
[0221] (8) Embodiment 8
[0222] In addition to using starch ((C 6 H 10 O 5 ) n +(H 2 The positive electrode active material was prepared in the same manner as in Example 1 except that sucrose was replaced by 2) as the carbon-based compound.
[0223] Table 1
[0224]
[0225] Experimental Example 1. Analysis of coating of positive electrode active material
[0226] In order to confirm the characteristics of the carbon coating layer formed on the positive electrode active material prepared according to Preparation Example 1, a TEM image was obtained using a scanning electron microscope and then shown in FIG. Figure 1 middle.
[0227] In addition, the thickness of the carbon coating formed on each positive electrode active material was measured 3 times, and the average value was calculated. The average coating thickness of each carbon-based compound in water at 25°C (B) and the ratio of the C element (A) (B / A) is shown in Figure 2 middle.
[0228] Reference Figure 1 and Figure 2 It can be confirmed that, unlike Examples 1 to 5 in which the B / A value is 10 or more, the coating thickness increases sharply in the Comparative Example in which the B / A value is less than 10.
[0229] Furthermore, it was confirmed that in Example 1 in which the B / A value was 30 or more, the coating thickness was particularly uniform.
[0230] Preparation Example 2. Preparation of lithium secondary battery
[0231] 94 wt % of each positive electrode active material prepared according to Preparation Example 1, 3 wt % of artificial graphite and 3 wt % of PVDF binder were dispersed in 3.5 g of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on an aluminum film having a thickness of 20 μm as a positive electrode collector and dried, and roll-pressed to prepare a positive electrode.
[0232] With respect to the positive electrode, a lithium foil was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and LiPF was used in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7. 6 The electrolyte was present at a concentration of 1.15 M to produce button cells using conventional manufacturing processes.
[0233] Experimental Example 2. Evaluation of electrochemical characteristics of lithium secondary batteries
[0234] In Preparation Example 2, a charge and discharge experiment was conducted on a button cell using an electrochemical analyzer (Toyo, Toscat3100) at 25°C, a voltage range of 2.0V to 3.65V, and a discharge rate of 0.1C to 5.0C, and the initial charge capacity, initial discharge capacity, energy density, initial reversible efficiency, and rate capability (discharge capacity ratio; rate capability C-rate) were measured. 3 g of the positive electrode active material was weighed in a granulator and the compression density was measured after pressurizing at 4.5 tons for 5 seconds. The energy density was calculated by multiplying the initial discharge capacity by the average voltage (3.4V) and the compression density.
[0235] Table 2
[0236]
[0237] Although the embodiments of the present specification are described above, those skilled in the art will understand that various modifications and changes can be made to the present specification by adding, modifying, deleting, increasing, etc., without departing from the scope of the ideas of the present specification as described in the claims, and these also fall within the scope of the rights of the present specification.
Claims
1. A method for preparing a positive electrode active material for a lithium secondary battery, characterized in that: include: Step (a), preparing a slurry by mixing a lithium-containing raw material, a transition metal precursor and a carbon-based compound; Step (b), crushing the particles in the slurry; and Step (c), heat treating the crushed particles to obtain lithium composite phosphorus oxide; The ratio (B / A) of the solubility (B) of the carbon-based compound in water at 25° C. to the ratio (A) of the C element is 10.00 g / (L·weight %) or more.
2. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the slurry in the step (a), a ratio (Li / Metal) of the number of lithium atoms (Li) to the total number of metal atoms (Metal) other than lithium is 0.95 to 1.
10.
3. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the slurry in the step (a), a ratio (C / Metal) of the number of carbon atoms (C) to the total number of metal atoms (Metal) other than lithium is 0.03 to 0.
1.
4. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The ratio (B / A) of the solubility (B) of the carbon-based compound in water at 25° C. to the ratio (A) of the C element is 30.00 g / (L·weight %) or more.
5. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The carbon-based compound is a compound in which the ratio (A) of the C element in the molecular structure is 30 wt % to 60 wt %.
6. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The solubility (B) of the above carbon-based compound in water at 25° C. is 0 g / L to 3,000 g / L.
7. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (a), at least one auxiliary raw material including an element selected from the group consisting of Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, F, Fe, Ga, Hf, I, In, K, La, Mg, Mo, N, Na, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr is further added to the above slurry.
8. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The average particle size (D50) of the particles pulverized in the step (b) is 1.0 μm or less.
9. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The particles pulverized in the step (c) are obtained by spray-drying the slurry obtained in the step (b).
10. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The heat treatment in the above step (c) is performed at a maximum temperature of 300° C. to 1,000° C. for 5 to 12 hours in an inert atmosphere.
11. A positive electrode active material for a lithium secondary battery, characterized in that: The invention comprises primary particles composed of lithium phosphorus composite oxide and secondary particles formed by agglomeration of a plurality of the primary particles. The primary particles are spherical in shape, and an amorphous carbon coating layer with a thickness of 1 nm to 30 nm is formed on at least a part of the surface of the primary particles.
12. The positive electrode active material for lithium secondary battery according to claim 11, characterized in that: The lithium composite phosphorus oxide is represented by the following chemical formula 2: [Chemical formula 2] Li p M x A y B z Q 1-z O w In the above formula, M is at least one selected from the group consisting of Fe, Mn, Ni and Co, A is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Na, Nb, Nd, Os, Pd, Pr, Pt, Rh, Ru, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, B is at least one selected from the group consisting of C, Si, S, N, B, F, Cl and I, 0.5≤p≤1.5, 0 <x≤1、0≤y<1、0≤z<1、0<w≤4。 13. The positive electrode active material for lithium secondary battery according to claim 11, characterized in that: The carbon coating layer may be contained in an amount of 1.4 wt % to 1.8 wt % based on 100 wt % of the lithium composite phosphorus oxide.
14. A positive electrode, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 11 to 13.
15. A lithium secondary battery, characterized in that: The positive electrode according to claim 14 is used.